Role of Nurse in Decrease Burden of Caregivers of Older Persons with Dementia - อุดมลาภ, รุ่งนภา (Journal of The Royal Thai Army Nurses, 2019)
The disease progression of dementia, which have been linked to declining memories and activities of daily living with mood and behavior changes that declining relationship for older persons with dementia and spouse caregivers who are not understand each other. Spouse caregivers may respond to these declining relationship with stress and burden. Nurses can play a pivotal role in providing care to older persons with dementia and caregivers by giving education, counseling, support and collaboration. These caring help the caregivers to understand and be able to provide proper care for the patients. Furthermore, the patients and caregivers understand each other that is good for the caregivers to care the older persons with dementia effectively.